2005
DOI: 10.1002/jssc.200500127
|View full text |Cite
|
Sign up to set email alerts
|

The use of tryptic marker‐peptides for the quantitative analysis of Cystatin C

Abstract: The use of marker-peptides, measured by LC-MS/MS, is investigated for the quantitative analysis of proteins. To that end, cystatin C is chosen as a model protein. It not only functions as a proof of concept protein but the growing interest in cystatin C as a new marker of kidney failure provides a practical application at the same time. The use of trypsin-based proteolysis, to obtain so-called marker-peptides, simplifies the quantification of a protein to the quantification of a single or a number of peptides.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Unfortunately, no real improvement in sensitivity was seen in our system. Experiments, however, with tryptic digests of cystatin C on a 2.1 mm LC-MS system revealed a twofold to threefold increase in sensitivity when using methanol instead of ACN [25]. At this moment, we cannot find a suitable explanation for these contradictory findings.…”
Section: Resultsmentioning
confidence: 53%
“…Unfortunately, no real improvement in sensitivity was seen in our system. Experiments, however, with tryptic digests of cystatin C on a 2.1 mm LC-MS system revealed a twofold to threefold increase in sensitivity when using methanol instead of ACN [25]. At this moment, we cannot find a suitable explanation for these contradictory findings.…”
Section: Resultsmentioning
confidence: 53%
“…Independently, two QC samples of 37.5610 2 pmol/mL (50.0 lg/mL, QC 1 ) and 374 pmol/mL (5.00 lg/mL, QC 2 ) were also prepared. Marker peptides were generated using Promega Sequencing Grade Modified Trypsin (lyophilized powder, Leiden, The Netherlands) according to an earlier published method [11]. To that end, cystatin C is denatured for 1 h at 658C using a solution of 8 M guanidine -HCl, buffered to pH 8 (Sigma, Bornem, Belgium).…”
Section: Chemicalsmentioning
confidence: 99%
“…Additionally, the method was tested on cystatin C marker peptides, obtained after in-solution trypsinization according to a previously published method. Cystatin C is a 146 aminoacid (aa) protein of 13.3 kDa and was chosen as a model protein [11].…”
Section: Lc (Tandem) Ms (Lc-ms(/msmentioning
confidence: 99%
“…Although more complex and less robust compared to the common immunochemical methods, it is less prone to cross-reactivity and has a competitive sensitivity. It has been demonstrated that several proteins like prions in brain tissue [7], the kidney dysfunction marker cystatin C [8], hemoglobin A2 in whole blood and dried blood spots [9], as well as the potential serum biomarker for prostate cancer Zn-a2 glycoprotein [10] can be quantitatively determined by this approach. Determination was achieved by first subjecting the sample to tryptic digestion and then subse-quently monitoring tryptic peptide(s) specific for the proteins to be determined.…”
Section: Introductionmentioning
confidence: 98%